2014
DOI: 10.1007/s10823-013-9221-6
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Differences in Perceptions of Heritage Tourism Among the Maasai of Tanzania

Abstract: Besides wildlife tourism in the African savannah, cultural heritage tourism (sometimes known only as heritage tourism) is a big draw in Tanzania. In order to attract cultural tourism dollars, Maasai communities have established cultural bomas, typically pseudo Maasai villages where they display cultural performances and crafts before tourists. Such cultural contact has resulted in the growing influence of globalization that challenges traditional ways. The economic, social and environmental impact of heritage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…We also emphasize that the situation of the Maasai is perhaps particularly troubling given on-going “land grabbing” conflicts (reviewed in [19] ), and the widespread commodification of their culture for profit, both inside and outside of Tanzania. Studies of the impact of cultural tourism attractions, such as so-called “cultural bomas”, where Maasai pose for photographs, sing, dance and sell handmade products to tourists in an artificial settlement, indicate a complex mix of benefits and costs to local communities [16] , [17] , [68] . Moreover, it has been estimated that many foreign companies made multi-million dollar profits in the last decade from Maasai-themed products, ranging from clothing and bed covers, to car accessories and stationary, capitalising on the exotic image of the Maasai to a western audience [69] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also emphasize that the situation of the Maasai is perhaps particularly troubling given on-going “land grabbing” conflicts (reviewed in [19] ), and the widespread commodification of their culture for profit, both inside and outside of Tanzania. Studies of the impact of cultural tourism attractions, such as so-called “cultural bomas”, where Maasai pose for photographs, sing, dance and sell handmade products to tourists in an artificial settlement, indicate a complex mix of benefits and costs to local communities [16] , [17] , [68] . Moreover, it has been estimated that many foreign companies made multi-million dollar profits in the last decade from Maasai-themed products, ranging from clothing and bed covers, to car accessories and stationary, capitalising on the exotic image of the Maasai to a western audience [69] .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their proximity to the major East African game parks and their distinctive customs and dress, the Maasai have become perhaps the most globally recognizable ethnic group in sub-Saharan Africa [15] . Indeed they are commonly (mis)represented in advertisements and tourist commercials for both Kenya and Tanzania, and in recent years have become the focus of a burgeoning cultural tourism economy [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…These elements, which can have a value of their own (value-in-self) and/or be allotted value as a part of a contextual story (value-in-context) (Heras et al, 2013;McDonald, 2011) bring heritage experience value to a region or a place (Hargrove, 2002), which in line with the association theory of cognitive psychology (Neisser, 1976) spill over to other visitor attractions. Thus, a positive relationship between the heritage value of tourism destinations and perceived authenticity of visitor attractions are assumed (Kalavar, Buzinde, Melubo, & Simon, 2014;Yankholmes & Akyeampong, 2010;Poria, Butler, & Airey, 2003). Following this line of reasoning the second hypothesis is:…”
Section: Perceived Tourism Destination Experience Value and Authenticitymentioning
confidence: 97%
“…Trust in this study is used to connote the government role in creating an enabling environment for citizens to participate in income generation through participation in domestic tourism. Lie and Peters (2016), Zaidan (2016), Moyle (2016) and Kalavar et al (2014) analyzed the component in different contexts, ranging from social capital, culture differences and social interactions. According to Nunkoo and Fung So (2015), the core components of the Social Exchange theory, namely trust, and the additional variable such as destination visit have to be considered simultaneously by researchers for a more accurate of residents' participation in tourism.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Hence researchers should test the components in an integrative framework. Kalavar et al (2014) used SET to analyze the economic, social and environmental impact of heritage tourism on the intergenerational relationship and community well-being. The study revealed that economic change appears to have created social distance between generations (Kalavar et al, 2014).…”
Section: Trustmentioning
confidence: 99%